Presencia de Cryptococcus fagisuga Lindinger (Homoptera: criptococcidae) en España - Soria, S.=700 1 Cadahia, D.; Carrascal, J.F.
(Es, En)
Ilus., 7 ref.
Keywords: FAGUS SYLVATICA; INSECTOS DAÑINOS; PLAGAS DE PLANTAS; ESPAÑA; CRIPTOCOCCUS FAGISUGA